Looking beyond adsorption energies to understand interactions at surface using machine learning - Agarwal, Sheena; Joshi, Kavita (ChemistrySelect, 2022)
Identifying factors that influence interactions at the surface is still an active area of research. In this work, the importance of analyzing bond length activations (BLact) along with adsorption energies (E-a) while interpreting Density Functional Theory (DFT) results is emphasized. Investigating adsorption of different small molecules, such as O-2, N-2, CO, and CO2, on commonly studied facets ((100), (110), and (111)) of seven fcc transition metal surfaces (M=Ag, Au, Cu, Ir, Rh, Pt, and Pd) demonstrates the missing linear correlation between E-a and BLact. Further, tree based Machine Learning (ML) models reinforce the missing linear correlation between the two parameters and also highlight the importance of analyzing both to develop a better understanding of adsorption at surfaces. The best performing Random Forest models have a mean absolute error (MAE) of 0.19 eV for E-a prediction, and even lower MAE of 0.012 angstrom for BLact prediction. While often d-band center is correlated with E-a, our observations show that infact the d-band center has a better correlation with BLact. These observations emphasizes the role of BLact in gaining a fuller picture for catalysis. The fact that the factors responsible for BLact is a lesser-explored subject adds to the novelty of the findings.
Keywords: Adsorption energy; Bondlength activation; catalysis; DFT; machine learning

Functionalized Mo2BX2 (X = H, OH, O) MBenes as a promising sensor, capturer and storage material for environmentally toxic gases: A case study of 1T and 2H phase - Shukla, Aarti; Sharma, Gautam; Krishnamurty, Sailaja (Applied Surface Science, 2023)
MBenes analogous to MXenes, exfoliated from the bulk MAB phase (M = transition metal, A = IIIA and IVA group, and B = boron) have appeared as promising two dimensional (2D) materials due to their intriguing properties. Here, we report the 2D 1T-2H-phase of Mo2B with their functionalized derivatives Mo2BX2 (X= H, OH, O) and investigate their structural, electronic, and adsorption behavior of toxic gases using the first-principles calculations. This study finds that pristine and functionalized MBenes have dynamic and thermal stability and possess metallic nature in both phases. Based on adsorption behavior and comparison with other 2D materials, we find that pristine MBenes are a desirable adsorbent for NO2, SO2, and CO2 capture. In contrast, the moderate adsorption energies for functionalized MBenes-NH3 systems reveal good sensitivity for NH3 gas detection in both phases. In particular, 2H-Mo2BH2 has higher CT (-0.11e) and appropriate adsorption energy (-0.30 eV), leads a shorter recovery time. Further, DOS calculations reveal that the electrical conducting behavior of MBenes makes them suitable for NH3 detection with a short recovery time. Our results would provide the first insight into the surface-functionalized effect on the structural and electronic properties of the MBenes, and shed light on the application of MBenes for the sensing and catalyst of typical toxic and greenhouse gases, respectively.
Keywords: Adsorption energy; First-principles study; Functionalization; Gas sensing; MBenes